Branching the risks: architectural plasticity and bet‐hedging in Mediterranean annuals. (17th December 2012) - Shemesh, H.; Novoplansky, A.
Abstract: It has been suggested that architectural plasticity in shoot size and number allows plants to manage environmental risks. Simpler structures require shorter development times and fewer resources, which secure minimal fitness even under risky and unfavourable conditions. Here we tested the hypothesis that the magnitude of such architectural plasticity depends on the species' developmental strategy. Specifically, species with late reproduction were expected to express the highest levels of architectural plasticity in response to environmental cues predicting high probability of abrupt deterioration in growth conditions. This hypothesis was tested by comparing Mediterranean and semi‐arid populations of three species, which differed in growth strategy: Trifolium purpureum, a determinate and late flowerer, and Emex spinosa and Hippocrepis unisiliquosa that flower indeterminately throughout the season. All plants were exposed to varying levels of water availability and competition, but only T. purpureum displayed plastic architectural responsiveness to the experimental manipulations. In contrast, the early and extended step‐by‐step flowering of both E. spinosa and H. unisiliquosa reflected a relatively deterministic bet‐hedging reproductive schedule, whereby minimum fitness is secured even under adverse conditions. These two opposing strategies gave contrasting results, with E. spinosa and H. unisiliquosa displaying reduced efficiency under favourable conditions under which T. purpureum had the highest reproductive efficiency. The evolutionary interplay between deterministic risk‐averse and plastic risk‐prone growth strategies might reflect contrasts in the probability and severity of environmental risks, and the costs of missed opportunities.